Effect Of Honey On Gentamicin Induced Nephrotoxicity In Albino Rats - DR KALYAN S. CHILWANT,; DR.MUGLIKAR A. G., (International Journal of Pharma and Bio Sciences, 2012)
The present study investigates the Nephroprotective effect of honey in albino rats. Assessment of renal damage induced by Gentamicin was done by using biochemical and histological parameters.